Cinnamon and cassia - Ravindran, P.N. (CRC Press LLC, 2011)
Cinnamon and Cassia, the "Spices of Life", together constitute one of the most widely used group of spices. A comprehensive volume, Cinnamon and Cassia: Genus Cinnamomum explores in detail Srilankan cinnamon, Chinese cassia, Indonesian cassia, Indian cassia, camphor, and also the important related and useful spices of Cinnamomum.